Death due to Occupational Accident a Report of Two Cases - Bütün, Celal; Beyaztaş, Fatma Yücel; Yaman, Sema; Artar, Adem; Öğüt, Oğuzhan (The Bulletin of Legal Medicine, 2015)
Today’s rapid technological developments increase, also the risks to worker’s health and work safety. Occupational accidents occurred with reasons such as necessary safety measures in work environment, incorrect behavior, inability on personal skills, technical failures result in bodily injury, loss of labor, disability or death. In this study; two male death cases aged 27 and 39 occured as a result of work accident in the area at the chrome mines were discussed. On the cases, physical examination, forensic autopsy and post-mortem examinations were performed. Event-related findings are similar; the cases were evaluated, together. It was determined that, respectively, cyanotic appearance on facial area and the front of the neck, the hyperemia on the sclera during external body examinations; in places punctuated hemorrhages under the skin and on the visceral organs’ surfaces during the autopsies; hemorrhage in subarachoidal area of the brain, hemorrhage on pleural areas of the lungs, sub-mucosal bleeding and congestion in the stomach during the post-mortem histopathology. Finally, the death cause of cases was due to lack of oxygen. In this study; also taking into account of work accident related injuries and deaths seen hight rates in our country, the determination of personal, socio-economic and enviromental factors and, the importance of taking the necessary measures for prevention of occupational accident were emphasized. Also, it aimed to be discussed forensic medical approach to occupational injuriy cases in the literature. Key Word: Forensic medicine, Work accident, Asphyxia, Death, Autopsy.